Use of Baccharis sylvestris species by indigenous Pankararu people: from traditional practices to pharmacological perspectives - a brief review (Research, Society and Development, 2023)
Historically, traditional knowledge has been the starting point for innovative research on medicines. However, the ethnopharmacological potential related to the use of some species, such as alecrim-de-caboclo, by the Pankararu people is still ignored by the scientific community. In view of the above, the objective of this article was to compile studies that report the use of rosemary-of-boaboclo by the indigenous people of the Pankararu ethnicity, speculating its pharmacological potential based on traditional knowledge. A literature review was conducted in the PubMed, Scielo and Google Academic databases. Only 13 articles were considered relevant to the present study, 10 directly related to the traditional use of alecrim-de-caboclo by the Pankararu people: and 3 related to divergences in the botanical classification of the species in other ethnic contexts. In 10 studies the traditional use of alecrim-de-caboclo for ritualistic purposes (80% of the studies) was reported, as well as its medicinal use (70% of the studies). Although therapeutic indications were not described, use in the form of a lick suggests traditional indication for colds and flu. Of the 10 studies, only 2 identified the species used by the Pankararu indigenous people as Baccharis sylvestris. Another 3 studies, conducted in other ethnic contexts, identified the rosemary as Lippia thymoides or Turnera diffusa. Further studies need to be conducted to perform a more detailed ethnopharmacological description of the alecrim-de-caboclo in the context of the Pankararu people, including traditional indications, taxonomic confirmation, phytochemical characterization, toxicity studies, and investigation of pharmacological potentials.